2013
DOI: 10.1038/nm.3358
|View full text |Cite
|
Sign up to set email alerts
|

A new cloning and expression system yields and validates TCRs from blood lymphocytes of patients with cancer within 10 days

Abstract: Antigen-specific T cell therapy, or T cell receptor (TCR) gene therapy, is a promising immunotherapy for infectious diseases and cancers. However, a suitable rapid and direct screening system for antigen-specific TCRs is not available. Here, we report an efficient cloning and functional evaluation system to determine the antigen specificity of TCR cDNAs derived from single antigen-specific human T cells within 10 d. Using this system, we cloned and analyzed 380 Epstein-Barr virus-specific TCRs from ten healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 24 publications
2
75
0
Order By: Relevance
“…These reports also showed that T cells modified with an antigen-specific TCR gene have excellent prospects for application in clinical practice. 42 In this report, we found that the TRBV families TRBV5.1, BV11, BV13.1, BV15, BV20 and BV24 were more frequently expanded monoclonally than other TRBV family members in recovered AHI subjects, regardless of the presence of CDR3 in the CD4 1 or CD8 1 T-cell subsets, further demonstrating that the T-cell immune response was polyclonal and polyspecific in the recovered AHI subjects studied. 43 This phenomenon was also discovered in the peripheral blood of patients with chronic …”
mentioning
confidence: 49%
“…These reports also showed that T cells modified with an antigen-specific TCR gene have excellent prospects for application in clinical practice. 42 In this report, we found that the TRBV families TRBV5.1, BV11, BV13.1, BV15, BV20 and BV24 were more frequently expanded monoclonally than other TRBV family members in recovered AHI subjects, regardless of the presence of CDR3 in the CD4 1 or CD8 1 T-cell subsets, further demonstrating that the T-cell immune response was polyclonal and polyspecific in the recovered AHI subjects studied. 43 This phenomenon was also discovered in the peripheral blood of patients with chronic …”
mentioning
confidence: 49%
“…This approach may be further enhanced by the development of techniques such as sorting with specific MHC tetramers to increase the frequency of mutation-reactive T cells from bulk TILs that may contain significant numbers of non-tumor reactive cells (34). Alternatively, TCRs isolated from cells reactive with mutated epitopes can be isolated and introduced into autologous peripheral blood T cells for the subsequent adoptive T-cell transfer (35, 36). …”
Section: Discussionmentioning
confidence: 99%
“…Not only are we able to study dual TCR expression, using this method we also can delineate the different (productively rearranged) TCR-a chains of a single T cell. Compared with other strategies that aim to validate functional TCRs from single T cells (15,16), our approach includes the directed cloning of amplified variable regions into IVT vectors providing the TCR-a/b constant regions for extremely rapid generation of full-length TCRs for validation assays that include the determination of epitope specificity for any antigen. Although next-generation sequencing-based methods and the use of barcodes allows for identification of potentially hundreds of a/b-TCRs in a single experiment (22), validation of these TCRs still requires subsequent cost-intensive gene synthesis and cloning.…”
Section: Discussionmentioning
confidence: 99%